Memorandum of understanding between Universiti Teknologi MARA and Politeknik Indonusa Surakarta / Fakulti Farmasi - Universiti Teknologi MARA, Fakulti Farmasi (Universiti Teknologi MARA (UiTM), 2020)
UiTM and Politeknik Indonusa Surakarta endeavour to take necessary steps to encourage and promote cooperation.